Evalution of Humoral Immune Response to vaccination with different strains against Newcastle Disease in broiler chickens (Journal of Hama University, 2019)
The research is  objected to evalution of Humoral Immune Response to vaccinate with different strains against Newcastle Disease in broiler chickens.Three groups of broiler chickens of one day age are rearing to fourty two days, and each group is including 100 bird.First group (control ) is  unvaccinated, second group is vaccinated with Lasota at ( 7-21-30) days , third group was vaccinated with clon30  at ( 7-21-30) days, fourth group is  vaccinated with B1 at ( 7-21-30) days.The HI test is used to measure  antibody titres of Newcastle disease at ( 1-18-28-42) days.The results are show that antibody titres are high in one day  in all groups and decrease in second, third  and fourth groups at 18 day compared with first group and it is a significant differences (P < 0.05 ) and that second group  vaccined with Lasota vaccine is give high antibody titres compared with three group vaccinated with clon30 and fourth group vaccinated with B1.The study show  that second group vaccined with Lasota vaccine is given high antibody titres compared with other groups and without significant differences (P < 0.05 ).